2012
DOI: 10.1161/atvbaha.112.252957
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is Associated With Atherosclerosis in Middle-Aged and Elderly Chinese

Abstract: Objective-To evaluate the associations between nonalcoholic fatty liver disease (NAFLD) and atherosclerosis. Methods and Results-A total of 8632 participants aged ≥40 years from Jiading district, Shanghai, were included in the present study. The presence of NAFLD was evaluated by ultrasonography. Carotid intima-media thickness (CIMT) and brachial-ankle pulse wave velocity (ba-PWV) were measured in each participant. The prevalence of NAFLD was 30.0% in the total population, with 30.3% in men and 29.9% in women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 29 publications
3
77
0
Order By: Relevance
“…[18][19][20] In addition, fatty liver and CAD share common risk factors like diabetes, obesity, dyslipidemia, hypertension etc. Also, carotid Doppler studies revealed higher intima media thickness in fatty liver patients which confirms the role of atherosclerosis causing similar plaques in coronary vessels and IHD [21] . In our study, the prevalence of nephropathy is slightly higher in the FL group but statically insignificant.…”
Section: Discussionsupporting
confidence: 62%
“…[18][19][20] In addition, fatty liver and CAD share common risk factors like diabetes, obesity, dyslipidemia, hypertension etc. Also, carotid Doppler studies revealed higher intima media thickness in fatty liver patients which confirms the role of atherosclerosis causing similar plaques in coronary vessels and IHD [21] . In our study, the prevalence of nephropathy is slightly higher in the FL group but statically insignificant.…”
Section: Discussionsupporting
confidence: 62%
“…Several studies have documented an association between NAFLD and increased risk of cardiovascular morbidity [20][21][22][23][24]. The association between ALT concentration and cardiovascular disease has also been well documented [12,13,25].…”
Section: Discussionmentioning
confidence: 96%
“…A total of 10,569 inhabitants were invited to participate in the survey. Among them, 10,375 residents signed the consent form and agreed to take part in the following detailed examination, with a participation rate of 98.2% ( 13,14 ). From these participants, we sequentially excluded subjects who met the following criteria: 1 ) those with missing data on their serum Lp(a) concentrations (n = 16) and/or fasting plasma glucose (FPG) and/or 2 h 75 g oral glucose tolerance test (OGTT) plasma glucose (2 hPG) levels and/or fasting serum insulin (FSI) levels (n = 36); 2 ) those with medical history of self-reported malignant tumors (n = 4); and 3 ) those with serious hepatic or renal dysfunction (n = 197).…”
Section: Study Population and Designmentioning
confidence: 99%